January Effect Phenomenon On Banking Companies Listed On The Indonesia Stock Exchange 2022-2023 - Permatasari, Anita; Ronadi, Violina Jasmine; Merryellen, Merryellen (DIPONEGORO UNIVERSITY, 2024)
The January effect is a seasonal anomaly that occurs in January only. Where in January the stock price increases higher than in other months. This study used quantitative research based on secondary data as the research design. The population used in this study are banking companies that are listed on the Indonesia Stock Exchange (IDX). The data used in this study are secondary data in the form of stock price data listed on the Indonesia Stock Exchange (IDX) in 2022-2023. The data was obtained from the Indonesia Stock Exchange (IDX) in the form of annual financial reports for 2022 to 2023 obtained from www.idx.co.id. The sample for this study was determined using the purposive sampling method. The results of the study showed that there was a January effect phenomenon in banking companies listed on the Indonesia Stock Exchange in 2022 to 2023.